Development and Validation of the Proxy-Reported Pulmonary Outcomes Scale for Premature Infants - Price, Wayne A.; Aliaga, Sofia R.; Massie, Sara E.; DeWalt, Darren A.; Laughon, Matthew M.; Malcolm, William F.; Van Meurs, Krisa; Klein, Jonathan M.; El-Ferzli, George; Magnus, Brooke E.; Tolleson-Rinehart, Sue (American Journal of Perinatology, 2015)
Objective Test the feasibility of using a bedside nurse–reported tool (Proxy-Reported Pulmonary Outcome Scale, PRPOS) for evaluating the severity of bronchopulmonary dysplasia (BPD) by assessing functional, disease-related measures.Study Design Bedside nurses tested the 26-item instrument by observing preterm infants (23–30 weeks at birth) at 36 to 374/7 weeks postmenstrual age before, during, and after a care time. We analyzed item reliability, validity, and model fit to determine the six items to include in the final measurement tool.Result We completed assessments on 188 preterm infants. The frequency of an abnormal PRPOS item score increased with increasing National Institute of Child Health and Development (NICHD) BPD category. The six-candidate items produced an internally consistent scale. Addition of the NICHD BPD classification increased reliability moderately; addition of feeding items decreased reliability. The PRPOS score correlated with postmenstrual age at discharge. Infants discharged on oxygen or diuretics had higher median PRPOS scores than did infants who were not prescribed those therapies.Conclusion The PRPOS is an internally consistent, proxy-reported measure of respiratory function in premature infants, based on observable, functional performance measures. Initial testing demonstrates known-groups validity and ongoing testing can assess predictive validity.
Keywords: bronchopulmonary dysplasia; infant; premature; outcome assessment; lung disease; neonatal